2021
DOI: 10.3389/fbioe.2021.677952
|View full text |Cite
|
Sign up to set email alerts
|

Are There Any Significant Differences in Terms of Age and Sex in Pedestrian and Cyclist Accidents?

Abstract: This study has analyzed sex-specific differences in pedestrian and cyclist accidents involving passenger cars. The most frequently injured body regions, types of injuries, which show sex-specific differences and the general accident parameters of females and males were compared. Accident data from three different European countries (Austria, Netherlands, Sweden) were analyzed. The current analysis shows that for both, females and males, pedestrian and cyclist injuries are sustained mainly to the body regions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…The differences in body shape, CoG and joint heights between the 50F and 50 M cause differences in the impact kinematics, impact locations of the different body parts and resulting injury risks as shown in Figure 8 , where the impact location of the hip and head are compared between the two models. In accordance with field data studies ( 32 ), a higher proximal femur fracture risk was observed in the simulations with the 50F compared to the 50 M (48% vs. 18% overall risk in the baseline cases). While the femur head of the 50F model hits directly the BLE for an impact at 40 km/h, the femur head of the 50 M hits the bonnet at a later stage and more horizontal angle ( Figure 8 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The differences in body shape, CoG and joint heights between the 50F and 50 M cause differences in the impact kinematics, impact locations of the different body parts and resulting injury risks as shown in Figure 8 , where the impact location of the hip and head are compared between the two models. In accordance with field data studies ( 32 ), a higher proximal femur fracture risk was observed in the simulations with the 50F compared to the 50 M (48% vs. 18% overall risk in the baseline cases). While the femur head of the 50F model hits directly the BLE for an impact at 40 km/h, the femur head of the 50 M hits the bonnet at a later stage and more horizontal angle ( Figure 8 ).…”
Section: Discussionsupporting
confidence: 89%
“…By comparing the field data with the predicted injuries, it was seen that, when comparing the data to in-depth databases which include more serious and fatal injuries [e.g., RAIDS database ( 74 )], the prediction is much more in line with the field data. Additionally, the distribution of injuries for the different body regions on AIS2+ level (lower extremities followed by the head and thorax) is in line with several studies ( 26 , 32 , 75 , 76 ), with respect that upper extremity injuries have not been evaluated in this study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies had discussed sexspecific differences. [8] (Table 01) Not only has sex been identified as a factor, but age has also been identified as a significant factor in determining the severity of injuries. Thus, it is emphasized that not only sex but also age, is a factor in determining the severity of pedestrian injuries in this study.…”
Section: Association Between Experiencing Pain and The Sex Of The Patient And Desire To Pursue Legal Actionmentioning
confidence: 99%
“…Another recent study shows that females are at a higher risk for moderate-severity injuries, especially in the extremities, even when differences in crash and vehicle type are considered ( Brumbelow and Jermakian, 2022 ). Sex-differences in injury patterns are also seen in vulnerable road users (VRU) crashes ( Leo et al, 2021 ). The reasons for these sex-differences are not apparent from the field data analyses.…”
Section: Introductionmentioning
confidence: 99%